HISTOPATOLOGI AORTA TORASIKA TIKUS PUTIH (Rattus novergicus strain wistar) JANTAN SETELAH PEMBERIAN DIET ATEROGENIK SELAMA 12 MINGGU - Sutrisno Tambunan; Enikarmila Asni; Zulkifli Malik (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTUnhealthy dietary pattern such as high fat diet and less of physical activity are the determinat of atherosclerosis. Atherosclerosis is a chronic inflammatory disease caused by lipid deposition in arterial wall. Beside the high fat consumption, addition of cholic acid and induction of vitamin D3 may also has role in atherosclerosis. Now, there has been many researches to know the process of the atherosclerosis using rat as animal model. The objective of this research is to know the differences of histopathologic image between thoracic aorta of male white rat (Rattus novergicus strain wistar) fed with standard diet and fed with atherogenic diet for 12 weeks. This research was an experimental laboratory with a post test only design. Twelve male rats were segregated into two groups (n=6) there were labelled as control group fed a standard diet and labelled as atherogenic group fed vitamin D3 and atherogenic diet which contain cholic acid 0,2%, fat 5% and yolk 2%. The experiment was designed for 12 weeks. The parameter used is atherosclerosis lesion score of all groups labelled. The result showed at control group found macrophage, foam cell and intracellular lipid accumulation with 33,33% percentage while atherogenic group found macrophage, foam cell and intracellular lipid accumulation with 100% percentage, extracellular lipid accumulation 33,33% (for a little extracellular lipid), 66,66 (a lot of extracellular lipid) and surface defect with 0,16%. The statistic test result showed the significant difference of atherosclerosis score between control group and atherogenic group (p=0,003). The conclusion of this study there is atherosclerosis process happen in 2 sampel (33,33%) in control group and 6 sampel (100%) in atherogenic group.Keywords : thoracic aorta, atherosclerosis, atherogenic diet, histopathology.